Green Economic Strategy: Mangrove Ecotourism Guide Training ForGen-Z In Kenagarian Sungai Pinang Pesir Selatan District: Strategi Ekonomi Hijau: Pelatihan Panduan Ekowisata Mangrove Bagi Gen-Z Di Kenagarian Sungai Pinang Kabupaten Pesir Selatan - Murhenna Uzra; Reffi Aryzegovina; Adipo Raman; Rahma Wahyudin (KPN Kopertis X, 2023)
Nagari Sungai Pinang is an area of Pesisir Selatan Regency that has Mangrove Ecotourism potential. This is the strategy of the Provincial Government and the South Coastal Government to make the Nagari Sungai Pinang area into an educational tourism center in the field of coral reef conservation and mangrove cultivation. However the problem is the very limited level of community education, coupled with the stigma of low learning motivation, means that the development of scientific literacy in mangroves in Nagari Sungai Pinang needs attention. The aim of this community service is to create a strategy for creating quality Tour Guides from Gen-Z and to make mangrove ecotourism a destination for tourists visiting Nagari Sungai Pinang. The steps built from this strategy are literacy given to nagari children with the concept of Green Economic Modeling as well as personal communication skills. They are members of the Andespin Youth Group community (Anak nagari Sungai Pinang Village). The number of members of this community is more than 200 people, the majority of whom are young people. The results of this activity make Green Economics an optimization of improving community welfare by utilizing mangrove forest resources, and making a good contribution to the environment. Thefuture output of this research is to produce Mangrove Tour Guides who are skilled and intelligent in promoting their nagari's tourism products, especially mangroves in the Nagari Sungai Pinang area, Pesisir Selatan Regency.